ANALISIS KINERJA KEUANGAN PENGELOLAAN ALOKASI DANA DESA BERDASARKAN RASIO EFEKTIVITAS DAN RASIO PERTUMBUHAN PADA KANTOR DESA KO’MARA KEC. POLONGBANGKENG TIMUR KABUPATEN TAKALAR - Nurdiana, Nurdiana; Nasrullah, Nasrullah; Amin, Amelia Rezki Septiani (LPPM - STIE SAKTI ALAM KERINCI, 2025)
This research aims to analyze the financial performance of village fund allocation management at the Ko'mara Village Office, Kec. East Polongbangkeng District. Calculation is based on the effectiveness ratio and growth ratio. The research method used is quantitative with financial ratio data analysis techniques. Village financial report data for the 2019 to 2023 fiscal year were processed using the SPSS version 29 application. The research results showed that the financial performance of village fund allocation management at the Ko'mara Village Office, District. East Polongbangkeng District. Takalar during the research period has not been effective and has not shown significant growth. Keywords: Financial Performance, Village Fund Allocation, Effectiveness Ratio, Growth Ratio